2011
DOI: 10.3389/fninf.2011.00004
|View full text |Cite
|
Sign up to set email alerts
|

Informatics and Data Mining Tools and Strategies for the Human Connectome Project

Abstract: NEUROINFORMATICSwith electroencephalography (MEG/EEG). A battery of behavioral and cognitive tests will also be included along with the collection of genetic material. This endeavor will yield valuable information about brain connectivity, its relationship to behavior, and the contributions of genetic and environmental factors to individual differences in brain circuitry. The data generated by the WU-Minn HCP consortium will be openly shared with the scientific community.The HCP has a broad informatics vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
490
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 614 publications
(492 citation statements)
references
References 29 publications
2
490
0
Order By: Relevance
“…Graphical depictions were created using the R‐package, ggplot2 [Ginestet, 2011]. Volumetric images were visualized with FSL tools (Oxford Centre for Functional MRI of the Brain, Oxford, United Kingdom), while surface‐based processing was performed using FreeSurfer [v5.3, Dale et al, 1999; Fischl et al, 1999a] and Connectome Workbench [v0.83, Marcus et al, 2011]. …”
Section: Methodsmentioning
confidence: 99%
“…Graphical depictions were created using the R‐package, ggplot2 [Ginestet, 2011]. Volumetric images were visualized with FSL tools (Oxford Centre for Functional MRI of the Brain, Oxford, United Kingdom), while surface‐based processing was performed using FreeSurfer [v5.3, Dale et al, 1999; Fischl et al, 1999a] and Connectome Workbench [v0.83, Marcus et al, 2011]. …”
Section: Methodsmentioning
confidence: 99%
“…This simulation indicated that, with an uncorrected threshold P < 0.001, a 76-voxel extent was sufficient to yield a corrected threshold of P < 0.05. For visualization, statistical maps were rendered on the cortical surface using Connectome Workbench (32).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the Human Connectome Project (HCP) [4,5] is accumulating vast amounts of image data in order to accelerate our understanding of brain function. This and predecessor programs such as the Bioinformatics Research Network (BIRN) [6,7] have established medical imaging firmly in the realm of big-data-based science.…”
Section: Introductionmentioning
confidence: 99%